ДЕВІАНТНА ПОВЕДІНКА СУБ’ЄКТІВ ЗОВНІШНЬОЕКОНОМІЧНОЇ ДІЯЛЬНОСТІ ТА ОСОБЛИВОСТІ ПРОТИДІЇ - Герчаківський, Святослав Дем’янович; Герчаківська, Ольга Ярославівна (Науковий журнал «Світ фінансів», 2017)
Герчаківський С. Д., Герчаківська О. Я. Девіантна поведінка суб’єктів зовнішньоекономічної діяльності та особливості протидії. Розглянуто сутність девіантної поведінки суб’єктів ЗЕД, її причини та прояви, виокремлено види девіантної поведінки та їх особливості. З’ясовано властивості та ознаки правопорушень, що характеризуються загальними рисами девіантної поведінки. Доведено, що порушення митних правил є одними з найбільш чисельних проявів девіантної поведінки суб’єктів ЗЕД в галузі державної митної справи. Проаналізовано способи ухилення від сплати митних платежів, особливості протидії таким деліктам в Україні та деяких країнах світу. Герчакивский С. Д., Герчакивская О. Я. Девиантное поведение субъектов внешнеэкономической деятельности и особенности противодействия. Рассмотрены сущность девиантного поведения субъектов ВЭД, его причины и проявления, выделены виды девиантного поведения, их особенности. Выяснены свойства и признаки правонарушений, у которых есть общии черты и признаки девиантного поведения. Доказано, что нарушение таможенных правил являются одними из наиболее многочисленных проявлений девиантного поведения субъектов ВЭД в области таможенного дела. Проанализированы способы уклонения от уплаты таможенных платежей, особенности противодействия таким преступлениям в Украине и некоторых странах мира. Gerchakivskyi S., Gerchakivska O. Deviant behavior of subjects of foreign economic activity and its counteraction. Introduction. Opposition deviant behavior in the customs area is one of the most important forms of fighting fiscal authorities with illegal manifestations measures to prevent customs offences, identify the causes and conditions contributing to commission of offenses and development of tax culture and education of citizens and subjects of foreign economic activity in the spirit of positive attitude to the established customs rules and regulations.Purpose. The aim of this article is to study the peculiarities of the implementation of the deviant behavior of subjects of foreign economic activity, the characteristic of evasion from payment of customs duties as one of the key customs of the deviations, and analysis of combating customs crime in Ukraine and the world.Results. Deviant behavior – the behavior of an individual or group that does not meet generally accepted standards, resulting in the violation of these rules. The problem of deviant behavior and its correction has always been important in pedagogy, psychology, criminology, but recently it becomes massive. Not an exception and customs sphere, the sphere of foreign economic activity, where the issues of offences, customs crime is extremely updated. Customs crimes is a special and specific group of crimes, therefore, against them criminal policy of our state forced to find also specific adequate to these crimes measures (means, methods) of their counteraction. Criminal policy must take into account two factors: first, the specificity of the criminalistic characteristics of crimes, in varying degrees, related to the violation of regulations for transportation of goods (items) through customs border of Ukraine; secondly, the sustainable development trend is the rapid escalation of customs offences from national to transnational. In different countries the variation in liability for evasion of customs payments is in the range from tarbolton relationship with extreme sanctions (for example, in China, provides execution) to failure to criminalize the acts under the laws of Switzerland. The specificity of customs crime objectively determines the search, and specific ways of its counteraction. Customs crime rather constantly changing, particularly under the influence of customs and criminal policy, so it changes (or should change) the mechanism of this counteraction.Conclusion. Fiscal authorities as the main subject of prevention of customs offences should be based on knowledge of the causes and conditions conducive to the commission of abuses in the customs area, customs fraud, the main trends of their distribution. Without studying these causes and conditions one cannot fully influence the condition of preventive activities and, hence, to ensure the effective development of the domestic customs system of the state.